2001
DOI: 10.1026//0012-1924.47.2.57
|View full text |Cite
|
Sign up to set email alerts
|

FAM: Ein Fragebogen zur Erfassung aktuller Motivation in Lern- und Leistungssituationen

Abstract: Zusammenfassung.Vorgestellt wird ein Fragebogen (FAM), der mit 18 Items vier Komponenten der aktuellen Motivation in (experimentellen) Lern- und Leistungssituationen erfasst, nämlich Misserfolgsbefürchtung, Erfolgswahrscheinlichkeit, Interesse und Herausforderung. Die deutsche sowie eine amerikanische Version weisen zufriedenstellende Konsistenzen auf (6 Stichproben, N = 944). Aus verschiedenen Experimenten liegen bereits Validitätshinweise dazu vor, dass die vorweg erfassten Motivationskomponenten mit dem nac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
122
0
21

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(144 citation statements)
references
References 8 publications
1
122
0
21
Order By: Relevance
“…Some other studies used the Questionnaire for Current Achievement Motivation assessing interest, subjective probability of success, challenge, and anxiety (Rheinberg, Vollmeyer, & Burns, 2001); it was found that current achievement motivation predicted performance on tests measuring general mental ability, knowledge acquisition, and complex problem solving (e.g., Freund & Holling, 2011;Vollmeyer & Rheinberg, 2000, 2006. It can be concluded from these results that current test motivation plays an important role in ability test performance, and poor test performance in a low-stakes setting cannot unambiguously be attributed to low ability alone (see Duckworth et al, 2011;Steinmayr et al, 2014).…”
Section: Current Test Motivation In Intelligence Testingmentioning
confidence: 99%
“…Some other studies used the Questionnaire for Current Achievement Motivation assessing interest, subjective probability of success, challenge, and anxiety (Rheinberg, Vollmeyer, & Burns, 2001); it was found that current achievement motivation predicted performance on tests measuring general mental ability, knowledge acquisition, and complex problem solving (e.g., Freund & Holling, 2011;Vollmeyer & Rheinberg, 2000, 2006. It can be concluded from these results that current test motivation plays an important role in ability test performance, and poor test performance in a low-stakes setting cannot unambiguously be attributed to low ability alone (see Duckworth et al, 2011;Steinmayr et al, 2014).…”
Section: Current Test Motivation In Intelligence Testingmentioning
confidence: 99%
“…Whereas this measurement procedure is meant to grasp cognitive load, another very similar measurement procedure is meant to grasp motivation. An example is given by Rheinberg et al (2001) who developed the questionnaire of actual motivation (QAM), which includes nearly the same kind of questions.…”
Section: Cognitive and Motivational Resourcesmentioning
confidence: 99%
“…The questionnaire consisted of 10 statements which had to be rated on a 5-point Likert scale to the extent that they applied to the participant in the current situation. Second, motivation was measured using the Questionnaire for Current Motivation (Rheinberg et al, 2001), which was adapted to the situation of BCI training. On a 7-point Likert scale participants rated items that assessed four different components of motivation: (1) mastery confidence, which indicated how much confidence a participant had that the training would be successful, (2) fear of incompetence, which indicated how much a participant feared to fail in the training, (3) interest, which indicated how interested the participant was in the training and (4) challenge, which indicated how challenging the participant considered the training.…”
Section: Psychological Variablesmentioning
confidence: 99%